Declining transition rates to psychosis: the contribution of potential changes in referral pathways to an ultra–high‐risk service. Issue 3 (14th November 2013) - Wiltink, Suzanne; Velthorst, Eva; Nelson, Barnaby; McGorry, Patrick M.; Yung, Alison R.
Abstract: Aim: On the basis of applying 'ultra–high‐risk' (UHR) criteria, initially high rates of transition to psychosis were reported. However, a decline in transition to psychosis has been observed in recent years. The current descriptive paper aims to investigate if this drop in transition rate may be due to potential changes in patterns of referral to a large UHR clinic. Methods: One hundred fifty young people who were referred to the Personal Assessment and Crisis Evaluation (PACE) Clinic in Melbourne, Australia, between August 2000 and July 2004 were included. Their referral pathways were assessed using a semistructured interview. Results were compared with a similar study of a cohort referred to the same clinic between 1995 and 1996. Results: The mean number of contacts prior to referral to the PACE Clinic was 1.93 (standard deviation (SD) = 1.15), and the average time between symptom onset and referral to PACE was 46.5 weeks (SD = 57.4). In comparison with the earlier cohort (mean = 2.36; SD = 1.32), our results indicate a lower number of contacts (Cohen's d = 0.35, r = 0.17). Furthermore, participants in the current study were referred twice as fast to the PACE Clinic. Conclusions: Increasing awareness of UHR symptoms among professionals and in the general population seems to have resulted in faster referral of young people to specialized mental health services. The global drop in transition rate might be due to a change in referral pathways to UHR services.